Rapid analysis of differential chemical compositions of Poria cocos using thin-layer chromatography spray ionization-mass spectrometry. Issue 13 (8th June 2022) - Yang, Ying; Li, Linnan; Li, Na; Li, Fan; Fan, Wenxiang; He, Yitian; Wang, Zhengtao; Yang, Li
Abstract : A simple analytical strategy for determining the chemical composition of Poria cocos using thin-layer chromatography spray ionization-mass spectrometry (TLCSI-MS). Abstract : Poria cocos, with medicinal and edible properties, contains multiple chemical components that pose difficulties in its quality control. Herein, we established a simple thin-layer chromatography spray ionization-mass spectrometry (TLCSI-MS) device that allows the simultaneous separation and identification of bioactive compounds. The triterpene acids in different medicinal parts of Poria cocos were characterized, and the markers of differences were revealed. The quantitative analysis of its pharmaceutical preparation has also been performed to verify the feasibility. The study provides a new analytical perspective for the screening and identification of multiple compounds and a good option for the quality evaluation of herbal medicines and foods.